Effect of the angiotensin-converting enzyme inhibitor zofenopril on ocular hydro- and hemodynamics in rabbits with experimental glaucoma (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the effect of the angiotensin-converting enzyme (ACE) inhibitor zofenopril on the intraocular pressure (IOP), rheographic quotient (RQ) and tonographic parameters of the eye in a rabbit model of adrenaline-induced glaucoma (AIG).Methods: In group 1 (12 animals), experimental glaucoma was induced by injecting 1:1000 adrenaline 0.1 ml through the auricle vein every other day for 3 months (40 injections totally). In group 2 (12 animals), glaucomatous animals received an aqueous suspension (1 ml) of zofenopril orally at a dose of 1 mg/kg daily for 3 months. The control group comprised 10 intact rabbits. Rabbit eyes were assessed by ophthalmoscopy and biomicroscopy. A Maklakoff tonometer was used for IOP measurements. Ocular hydro- and hemodynamics were assessed. The Kruskal-Wallis and Mann-Whitney tests were employed to assess group differences.Results: In group 1, mean IOP statistically significantly increased by 28.3%, 34.2% and 46.7% at days 30, 60 and 90, respectively, compared to baseline (р < 0.05). Additionally, mean IOP statistically significantly increased at all time points compared to controls. In group 2, at day 60 and day 90, IOP was 19.6% and 29.6% lower, respectively, compared to group 1. In non-treated glaucomatous animals, at day 90, RQ was decreased by 37.0%, tonographic aqueous humor (AH) outflow facility (C) was decreased by 36.8%, AH production was increased by 23.0% and tonographic IOP (P0) was increased by 61.4% compared to controls. In glaucomatous animals treated with zofenopril, at day 90, RQ and C were 45.7% and 41.7%, respectively, higher, and AH production and P0 were 24.1% and 22.4%, respectively, lower compared to non-treated glaucomatous animals.Conclusion: In rabbits with AIG, ocular blood flow and ocular hydrodynamics parameters were impaired in the presence of elevated IOP. Zofenopril had a beneficial effect on the function of eyes with AIG (i.e., the IOP, parameters of ocular hemodynamics and AH circulation).
Keywords: glaucoma; pathogenesis; ACE inhibitor zofenopril; intraocular pressure; ocular hydrodynamics; ocular hemodynamics; rheographic quotient; experiment